Lung Pathology of Mutually Exclusive Co-infection with SARS-CoV-2 and Streptococcus pneumoniae - Tsukamoto, Tetsuya; Nakajima, Noriko; Sakurai, Aki; Nakajima, Masayuki; Sakurai, Eiko; Sato, Yuko; Takahashi, Kenta; Kanno, Takayuki; Kataoka, Michiko; Katano, Harutaka; Iwata, Mitsunaga; Doi, Yohei; et al. (Emerging infectious diseases, 2021)
Postmortem lung pathology of a patient in Japan with severe acute respiratory syndrome coronavirus 2 infection showed diffuse alveolar damage as well as bronchopneumonia caused by Streptococcus pneumoniae infection. The distribution of each pathogen and the accompanying histopathology suggested the infections progressed in a mutually exclusive manner within the lung, resulting in fatal respiratory failure.